Language Attitudes and Minority Rights The Case of Catalan in France - Hawkey, James (Springer International Publishing, 2018)
This book presents a detailed sociolinguistic study of the traditionally Catalan-speaking areas of Southern France, and sheds new light on language attitudes, phonetic variation, language ideologies and minority language rights. The region's complex dual identity, both Catalan and French, both peripheral and strategic, is shown to be reflected in the book's attitudinal findings which in turn act as reliable predictors of phonetic variation. The author's careful discursive analysis paints a clear picture of the linguistic ideological landscape: in which French dominates as the language of status and prestige. This innovative work, employing cutting-edge mixed methods, provides an in-depth account of an under-examined language situation, and draws on this research to propose a number of policy recommendations to protect minority rights for speakers of Catalan in the region. Combining language attitudes, sociophonetics, discourse studies, and language policy, this will provide an invaluable reference for scholars of French and Catalan studies and minority languages around the world.